Primary Dealer Systems : Draft Background Note - World Bank (Washington, DC, 2016)
Primary dealer system can make substantial contributions to the development of the market when its establishment is appropriate for prevailing market conditions. While by no means a precondition for a well functioning government securities market, primary dealers know the market best and are the counterpart of the investors who are the debt management office’s ultimate target. The purpose of this background note is to provide some guidance on how to design a primary dealer system so as to best meet the development needs of the market as well as the legitimate expectations of the parties involved.